Analysis of Content Innovation, Ease of Access, and Technology Support on Generation Z User Engagement on Educational Platforms in Indonesia - Judijanto, Loso; Aldo, Novian; Fildansyah, Rully (Westscience Press, 2024)
This study examines the impact of content innovation, ease of access, and technology support on Generation Z user engagement with educational platforms in Indonesia. Employing a quantitative research approach, data were collected from 120 respondents using a structured questionnaire measured on a 5-point Likert scale. The Structural Equation Modeling-Partial Least Squares (SEM-PLS) method was used to analyze the relationships between the independent variables (content innovation, ease of access, and technology support) and the dependent variable (user engagement). The findings reveal that all three factors significantly and positively influence user engagement, with content innovation being the strongest predictor. These results underscore the importance of delivering innovative content, ensuring accessibility, and maintaining robust technology support to enhance user engagement. The study offers actionable insights for educational platform developers and contributes to the growing body of knowledge on digital education and user behavior, particularly in emerging markets such as Indonesia.